Understanding of Umm al-Ṣibyān (Childhood Epilepsy) through Classical and Holistic Approach - Mohd Bilal; Sabeeh; Md. Sohail (Traditional Medicine and Modern Medicine, 2025)
Childhood epilepsy is traditionally known as Umm al-Ṣibyān in the ancient Unani system of medicine, and it is one of the first documented medical illnesses affecting mankind. According to the World Health Organization (WHO), this chronic, non-communicable neurological illness can afflict people of any age. It is the most common neurological condition in the world, affecting 50 million people and resulting in approximately 5 million new cases each year. In 2022, there are expected to be 456,000 children aged 17 and under, who have active epilepsy. This traditional medical approach classifies Umm al-Ṣibyān based on temperament, the prevalence of specific humor, and internal and external contributory factors. This study aims to examine the Unani medical theoretical framework of Umm al-Ṣibyān, including its classification, aetiology, and management through the use of various Unani therapeutic modalities, such as Ilāj bi’l Taghdhiya, Ilāj bi’l Dawā’, and Ilāj bi’l Tadb[Formula: see text]r. The information gathered from this study is intended to contribute to the development of novel treatment strategies as well as the reduction of the prevalence of this neurological disorder among children globally.